EFFECT OF SALES PROMOTION ON BRAND LOYALTY GRABFOOD - Dinda Putri Damara; Indria Angga Dianita (Program Studi Administrasi Bisnis, Fakultas Komunikasi dan Bisnis, Universitas Telkom, 2023)
Sales Promotion is a sales promotion activity that is carried out at a certain time which is useful for increasing product sales. There are various tools in sales promotion that can be used including samples, coupons, cashback, price offers, premiums, promotional products, and sweepstakes, contexts, games. Forms of sales promotion activities on GrabFood services, namely cashback, price offers, and premiums. The purpose of this study was to determine the magnitude of the influence of Sales Promotion on Brand Loyalty GrabFood. The method used in this study is quantitative with the correlation coefficient test, the coefficient of determination test and data analysis techniques using simple linear regression analysis. The result of the correlation coefficient test is 0.632 so it can be concluded that sales promotion and brand loyalty have a strong relationship. In addition, it was found that there was a relationship between the sales promotion variable and the influence of brand loyalty by 40%, while 60% was influenced by other variables that were not in this study. There is a positive and significant influence on brand loyalty, as evidenced by the results of a simple linear regression test analysis of 1,440 on the sales promotion variable which has the effect that every 1% increase will affect the brand loyalty variable.